Pengelolaan Kelas dalam Pembelajaran - Zainal Azman (STAI Bumi Silampari, 2020)
Classroom management is a conscious effort to regulate the activities of the teaching and learning process systematically which leads to the preparation of facilities and teaching aids, the arrangement of the learning space, realizing the situation or condition of the teaching and learning process going well and the curricular objectives can be achieved. The ultimate goal of classroom management is students can develop self-discipline. Therefore, teachers should always encourage students to carry out self-discipline and the teacher himself should be an example of self-control and the implementation of responsibilities. So, teachers must be disciplined in everything if they want their students to be disciplined in everything.